Research on the formation mechanism of information cocoon and individual differences among researchers based on information ecology theory - Yuan, Xiaofang; Wang, Chunyun (Frontiers in Psychology, 2022)
Introduction Choosing to only retrieve and read academic information related to their own research field is conducive to researchers’ in-depth understanding of their own research issues, and also reduces the pressure of researchers’ information retrieval, but may bring about the effect of information cocoon. Methods Based on the information ecology theory, a theoretical model is built from the aspects of information people, information, information environment and information technology, and relevant data is collected through questionnaires to verify assumptions. To explore the formation path of information cocoon for scientific researchers and the differences between different types of scientific researchers. Results Different gender, education background, identity, age and team size of scientific researchers will lead to different dimensions in the process of producing information cocoon; Community influence, information homogeneity and value identification are important factors influencing the formation of information cocoon room for scientific researchers; Community influence and information homogeneity positively affect value identification. Discussion In the future research work, researchers should pay attention to the influence of information homogeneity, community influence and value identification.